2023
DOI: 10.3389/forgp.2023.1284650
|View full text |Cite
|
Sign up to set email alerts
|

Worker's compensation usage and return to work outcomes for Ontario public safety personnel with mental stress injury claims: 2017–2021

Megan Edgelow,
Santyna Brar,
Agnieszka Fecica

Abstract: This study explored approved worker's compensation claims made by public safety personnel (PSP) with work-related psychological injuries to the Workplace Safety and Insurance Board (WSIB) of Ontario's Mental Stress Injury Program (MSIP) between 2017 and 2021. This worker's compensation program provides access to health care coverage, loss of earnings benefits, and return to work support services for psychologically injured workers. In 2016, the Government of Ontario amended legislation to presume that, for thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Between January 1, 2016 and April 30, 2020, WSIB approved 5691 claims made by all PSP career categories under the presumptive PTSD legislation ( Conference Board of Canada, 2021 ). A recent study of WSIB claims made between 2017 and 2021 revealed that the number of claims in Ontario has grown, with significantly more claims made in 2021 (n = 1420) compared to 2017 (n = 1050) ( Edgelow et al, 2023a ). This study also revealed that the majority of approved claims were made by police (33.5%), paramedics (28.4%), and correctional workers (21.6%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between January 1, 2016 and April 30, 2020, WSIB approved 5691 claims made by all PSP career categories under the presumptive PTSD legislation ( Conference Board of Canada, 2021 ). A recent study of WSIB claims made between 2017 and 2021 revealed that the number of claims in Ontario has grown, with significantly more claims made in 2021 (n = 1420) compared to 2017 (n = 1050) ( Edgelow et al, 2023a ). This study also revealed that the majority of approved claims were made by police (33.5%), paramedics (28.4%), and correctional workers (21.6%).…”
Section: Introductionmentioning
confidence: 99%
“…This study also revealed that the majority of approved claims were made by police (33.5%), paramedics (28.4%), and correctional workers (21.6%). The remaining claims were made by firefighters (9.4%) and communicators (7.1%) ( Edgelow et al, 2023a ).…”
Section: Introductionmentioning
confidence: 99%